Did GRW Investment Grants Contribute to the Catching-up of East Germany? - Eva Dettmann; Matthias Brachert; Lutz Schneider; Mirko Titze (Wirtschaftsdienst)
Abstract The joint task force ‘Improving Regional Economic Structures’ (GRW) is the most important regional policy scheme in Germany and was extensively used to support the economic transformation process in the new states after reunification. The article provides an overview of national and international causal analytical studies on the effects of investment grants. The analysis shows that such programmes have positive effects on development — especially of employment and income. It not only affects the subsidised establishment benefit from this type of support, but the regions as a whole. Even though the studies do not go back to the early 1990s, we can conclude that the GRW contributed to economic development in East Germany — and to the catching-up process.